2014
DOI: 10.1021/nl500524w
|View full text |Cite
|
Sign up to set email alerts
|

Franck–Condon Blockade in a Single-Molecule Transistor

Abstract: We investigate vibron-assisted electron transport in single-molecule transistors containing an individual Fe 4 Single-Molecule Magnet. We observe a strong suppression of the tunneling current at low bias in combination with vibron-assisted excitations. The observed features are explained by a strong electron-vibron coupling in the framework of the Franck-Condon model supported by density-functional theory.Vibrational modes (vibrons) play an essential role in the mechanics of a wide variety of nanostructures. I… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
126
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 114 publications
(139 citation statements)
references
References 30 publications
12
126
0
Order By: Relevance
“…The features of transport characteristics are determined by the occupation of the levels, the transition rates, and the Franck-Condon factors, rather than the level broadening. This is supported by experimental observation of dominant sequential tunneling 28,40 , and it was also theoretically shown in the case of without electron-vibron coupling 54 . In addition, the vibrational excitation energies of interest are larger than the experimental level broadening.…”
Section: Discussionsupporting
confidence: 78%
See 2 more Smart Citations
“…The features of transport characteristics are determined by the occupation of the levels, the transition rates, and the Franck-Condon factors, rather than the level broadening. This is supported by experimental observation of dominant sequential tunneling 28,40 , and it was also theoretically shown in the case of without electron-vibron coupling 54 . In addition, the vibrational excitation energies of interest are larger than the experimental level broadening.…”
Section: Discussionsupporting
confidence: 78%
“…The previous DFT calculations suggest that the Fe 4 has only three vibrational modes with the electron-vibron coupling greater than unity 28 .…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation
“…Electronic transport through the system requires the electron number to change and hence the polarons to be broken up, which is energetically disfavored if the electron-vibron coupling that holds them together is strong. This effect has been observed in single-molecule junctions 19 as well as in CNT systems, 12 adding to the variety of ways in which material structure can influence conductance. In addition, it has also been shown that the coupling between the mechanical and electronic degrees of freedom can be tailored to some extent.…”
Section: Introductionmentioning
confidence: 93%
“…In addition, vibrational modes can couple to the charge carriers and therefore show up in conductance measurements. Figure 12(a) shows the dI/dV color plot of an Fe 4 junction in which vibrations appear as SET lines parallel to the diamond edges 39 . The measurements are performed at T = 1.8 K. The excitations can also be observed in the conductance plot in Figs.5(a) and 5(b).…”
Section: High-energy Excitations: Spin Excited Multipletsmentioning
confidence: 99%